2010
DOI: 10.1111/j.1548-1425.2010.01247.x
|View full text |Cite
|
Sign up to set email alerts
|

Being neurologically human today: Life and science and adult cerebral plasticity (an ethical analysis)

Abstract: Throughout the 20th century, scientists believed that the adult human brain is fully developed, organized in fixed and immutable function‐specific neural circuits. Since the discovery of the profound plasticity of the human brain in the late 1990s, this belief has been thoroughly undermined. In this article, combining ethnographic and historical research, I develop an “ethical analysis” to show that (and in what concrete sense) the emergence of adult cerebral plasticity was a major mutation of the neurological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…Celebrated as a revolutionary finding, and immediately taken up by a large spectrum of interested individuals from brain fitness dealers to philosophers and psychiatrists, political scientists, and rehabilitation specialists (Malabou, 2008;Ortega, 2011;Pitts-Taylor, 2010;Rees, 2010), neuroplasticity also seems to confirm that cultural differences at the neural level reside in patterns of connectivity. Sustained engagement in cultural tasks, understood as repeated participation in routinized behaviors, results in different patterns of brain activation and functional and structural modifications (see Hanawaka et al, 2003 for Japanese abacus experts, or Maguire et al, 2000, for London taxi drivers).…”
Section: Causes Correlations Plasticitymentioning
confidence: 95%
“…Celebrated as a revolutionary finding, and immediately taken up by a large spectrum of interested individuals from brain fitness dealers to philosophers and psychiatrists, political scientists, and rehabilitation specialists (Malabou, 2008;Ortega, 2011;Pitts-Taylor, 2010;Rees, 2010), neuroplasticity also seems to confirm that cultural differences at the neural level reside in patterns of connectivity. Sustained engagement in cultural tasks, understood as repeated participation in routinized behaviors, results in different patterns of brain activation and functional and structural modifications (see Hanawaka et al, 2003 for Japanese abacus experts, or Maguire et al, 2000, for London taxi drivers).…”
Section: Causes Correlations Plasticitymentioning
confidence: 95%
“…How, in other words, is the brain that is said to underpin our personhood being conceptualized within and beyond the neuroscientific laboratories? Brains that are emotional, brains that are neuroplastic, and brains that are characterized by mirror neurons are arguably beginning to make significant inroads into public discourse, and to be themselves subjected to critical interrogation (Rubin, 2009;Rees, 2010). But while the emergent field of resting state research is, as we have demonstrated, already making a significant impact both empirically and conceptually within the neurosciences, it has as yet not been subject to any sustained critical analysis from a perspective not wholly embedded within neuroscience.…”
Section: Paradigms Contrasted: the Subject (Not) At Restmentioning
confidence: 96%
“…5 Here one can see the overlaps between food and drug, a topic that Ecks (2014) takes up in detail. 6 Plastic also informs the concept of 'plasticity', a term from the biosciences that refers to an organism's ability to vary according to its surrounding environments (see, for instance, Landecker, 2007;Niewöhner, 2011;Malabou, 2008;Papadopoulos, 2011;Rees, 2010).…”
Section: Detecting the Reliability Of Elementsmentioning
confidence: 99%